Live Tissue Imaging to Elucidate Mechanical Modulation of Stem Cell Niche Quiescence - Yu, Nicole Y.C. (Stem Cells Transl Med, 2016)
The periosteum, a composite cellular connective tissue, bounds all nonarticular bone surfaces. Like Velcro, collagenous Sharpey's fibers anchor the periosteum in a prestressed state to the underlying bone. The periosteum provides a niche for mesenchymal stem cells. Periosteal lifting, as well as injury, causes cells residing in the periosteum (PDCs) to change from an immobile, quiescent state to a mobile, active state. The physical cues that activate PDCs to home to and heal injured areas remain a conundrum. An understanding of these cues is key to unlocking periosteum's remarkable regenerative power. We hypothesized that changes in periosteum's baseline stress state modulate the quiescence of its stem cell niche. We report, for the first time, a three‐dimensional, high‐resolution live tissue imaging protocol to observe and characterize ovine PDCs and their niche before and after release of the tissue's endogenous prestress. Loss of prestress results in abrupt shrinkage of the periosteal tissue. At the microscopic scale, loss of prestress results in significantly increased crimping of collagen of periosteum's fibrous layer and a threefold increase in the number of rounded nuclei in the cambium layer. Given the body of published data describing the relationships between stem cell and nucleus shape, structure and function, these observations are consistent with a role for mechanics in the modulation of periosteal niche quiescence. The quantitative characterization of periosteum as a stem cell niche represents a critical step for clinical translation of the periosteum and periosteum substitute‐based implants for tissue defect healing. Stem Cells Translational Medicine 2017;6:285–292